Behçet's disease presented with obscure gastrointestinal bleeding: A Palestinian case report - Afnan W. M. Jobran; Abdelrhman Janem; Tareq Alhor; Muhammad Idris; Mustafa Nabilsi; Salam Mughrabi; Aisha Alfakhry; Hazem Ashhab (Clinical Case Reports)
Key Clinical Message It is important to recognize and manage gastrointestinal symptoms in patients with BD, as they are linked to high rates of mortality and morbidity. BD can affect any part of the gastrointestinal tract, and prompt diagnosis and appropriate treatment are essential to prevent complications. Additionally, the diagnosis of BD is primarily based on clinical factors due to the lack of pathognomonic laboratory tests. Abstract Behçet's disease (BD) is an idiopathic, chronic, and relapsing multi‐systemic vasculitis characterized by recurrent skin lesions and eye disease. There is no pathognomonic laboratory testing; the diagnosis is made mainly on clinical factors. BD symptoms affecting the gastrointestinal (GI) system are particularly important as they are linked to high rates of mortality and morbidity. Although ileocecal involvement is most frequently mentioned, BD can affect any part of the GI tract. There are techniques for keeping track of disease activity during treatment, but they are not ideal. We present a case of a 38‐year‐old male patient admitted to the ICU with a history of black tarry stools of 1‐month duration, fresh blood per rectum 5 to 7 times a day associated with fever, chills, and back and nonspecific joint pain for five days. The patient also experienced left eye episcleritis while being hospitalized, which was later confirmed to be BD.